Holoprosencephaly-polydactyly ('pseudotrisomy 13') syndrome: a syndrome with features of hydrolethalus and Smith-Lemli-Opitz syndromes. A collaborative multicentre study. Issue 5 (May 1991) - Verloes, A; Aymé, S; Gambarelli, D; Gonzales, M; Le Merrer, M; Mulliez, N; Philip, N; Roume, J
Abstract : A syndrome of holoprosencephaly and postaxial polydactyly, associated with hydrocephalus, heart defect, adrenal hypoplasia, and other visceral malformations, has been observed in five unrelated children with normal chromosomes. Clinical overlap with lethal acrodysgenital dwarfism (Smith-Lemli-Opitz syndrome type II) and hydrolethalus syndrome is discussed. Recessive inheritance seems likely.